PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 008 TELUK JIRA KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Hardianti, Melisa; Lazim, Lazim; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to improve the learning outcomes of IPS students of class V SDN 008 Teluk Jira District Tempuling Indragiri Hilir by applying cooperative learning type of talking stick model. The method used in this research is classroom action research. Subjects in this study were the students of class V SDN 008 Teluk Jira District Tempuling Indragiri Hilir Regency in the academic year 2016/2017, and the number of students 29 people. Instrument used in this research is by using obseravasi sheet and test done at each end of cycle. This study was conducted in two cycles. From the data analysis, this research is an increase in student learning outcomes. This improvement is seen from the student's learning result before applying the talking stick teaching model that is 72.75 and increased to 77,58 in the second cycle. On the basic score, only 15 students (51.72%) reached KKM. In the first cycle, the number of students who reached KKM increased by 6.63% from the basic score that increased to 21 (72,41%). In cycle II the number of students who reached KKM increased by 17.30%. From cycle I to 25 students reaching KKM (86.20%). The same is true of student activity. In cycle I the percentage of student activity was 66.67% increasing by 4.16% to 70.83% in the second meeting of cycle I. At the first meeting of cycle II increased by 8.33% to 83.33%. In the second meeting, cycle II increased again by 8.34% to 91.67%. Based on data analysis in research that has been done that the application of cooperative learning model type of talking stick can improve learning outcomes and activities of class V students SDN 008 Teluk Jira Tempuling District Indragiri Hilir Regency. Keywords: Talking Stick, IPS Learning Results.